2012
DOI: 10.1111/j.1468-5876.2012.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

A Revisit to the Stationarity of Oecd Inflation: Evidence From Panel Unit-Root Tests and the Covariate Point Optimal Test*

Abstract: This paper re‐examines the stationarity of inflation rates in 19 Organisation for Economic Cooperation and Development countries with the use of cross‐sectional information. We employ the panel unit‐root tests that allow for cross‐sectional dependency and the covariate point optimal test. These tests have high power in common due to the exploitation of cross‐sectional information, and they can assist mutually to draw a concrete conclusion on inflation dynamics for all series in the panel. Our empirical results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
(154 reference statements)
0
1
0
Order By: Relevance
“…Another researcher, Osterholm (2004) showed the stationary of inflation rates in the United Stated of America by using three unit root tests, namely the IPS unit root test Im et al (2003) the MADF Taylor and Sarno (1998) and the Johansen (1988) test of the likelihood report. Tsong et al (2012) found reliable proof of the mean reversion of inflation rates of 19 OECD countries. For their investigation they utilise the panel unit root tests that allow a transversal dependence and the optimal test of the covariable point.…”
mentioning
confidence: 91%
“…Another researcher, Osterholm (2004) showed the stationary of inflation rates in the United Stated of America by using three unit root tests, namely the IPS unit root test Im et al (2003) the MADF Taylor and Sarno (1998) and the Johansen (1988) test of the likelihood report. Tsong et al (2012) found reliable proof of the mean reversion of inflation rates of 19 OECD countries. For their investigation they utilise the panel unit root tests that allow a transversal dependence and the optimal test of the covariable point.…”
mentioning
confidence: 91%